Análise da eficiência e alocação dos fatores de produção na Zona Franca de Manaus - Gouvêa, Alexandre Pereira Espírito Santo de (Brasil, 2024)
This study aimed to analyze the variation in efficiency levels and productivity of 11 industrial subsectors located in the Manaus Industrial Pole in the pre-pandemic, during, and post-pandemic years, particularly from 2018 to 2022. More specifically, it aimed to measure the efficiency of the subsectors and verify the Total Factor Productivity (TFP) through the Malmquist index. To do this, the non-parametric technique of Data Envelopment Analysis (DEA) was used, with product orientation and through the Variable Returns to Scale (BCC) model. The data from Decision Making Units (DMUs), inputs, and products were from the Performance Indicators of the Manaus Industrial Pole (PIM) report prepared by the Superintendence of the Manaus Free Trade Zone (SUFRAMA). The results showed that the subsectors of the PIM, together, were not efficient in any of the years evaluated. However, certain subsectors, individually, were efficient over the years studied. Furthermore, it was found that the pandemic brought significant con